Verhaltensweisen von Lehrkräften im Umgang mit Schülerfehlern – Ergebnisse einer empirischen Studie (mathematica didactica, 2022)
Teachers’ behaviours in dealing with student errors in the context of mathematics education are a central topic in mathematics didactics. Nevertheless, there are only few empirical studies on the topic, especially from recent times. In the present study, this research deficit is addressed. For this purpose, based on videotaped mathematics lessons of 13 Hamburg teachers over two double lessons, different behaviours in dealing with student errors are reconstructed. In this context, pragmatic ways of dealing with student errors – advancing in the teaching process – versus process-oriented ways of dealing with student errors – aiming at understanding processes – are compared. We were able to reconstruct the following behaviours of teachers in dealing with errors in an ideal-typical way and exemplify them with examples from the classroom: Passing on the error or the question, help in correcting the error, and focusing on the wrong issue in the pragmatic approach; use of general-strategic help, content-oriented strategic help, and content-related help as well as focusing on the right issue in the process-oriented approach. Thereby, a dominance of pragmatic ways of dealing with errors could be reconstructed, although there are clear individual differences among the teachers. Furthermore, differences in the chosen ways of dealing between the teaching phases cannot be clearly identified.